Vận dụng phương pháp giáo dục của Chủ tịch Hồ Chí Minh vào giảng dạy các môn Lí luận chính trị trong nhà trường quân đội hiện nay - Vũ , Đình Lực (Tạp chí Giáo dục, 2023)
In the process of building a lean, compact, strong and specialized Vietnamese people's army, meeting the requirements of national defense in the new situation, the study and application of President Ho Chi Minh's educational methods in improving the quality of teaching political theory subjects in military schools is one of the most important and urgent contents today. Based on the study of President Ho Chi Minh's speeches and articles related to education, the article outlines the basic arguments about his educational methods, as a theoretical basis for the application and proposal of solutions to improve the teaching quality of political theory subjects in military schools today. These are lessons and practical educational experiences that are very vivid, practical and effective for educators in particular and the education industry in general today, helping to improve the quality of teaching Political theory subjects in military schools.